2010
DOI: 10.1007/s11858-010-0251-z
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming intuitive interference in mathematics: insights from behavioral, brain imaging and intervention studies

Abstract: It is well known that many students encounter difficulties when solving problems in mathematics. Research indicates that some of these difficulties may stem from intuitive interference with formal/logical reasoning. Our research aims at deepening the understanding of these difficulties and their underlying reasoning mechanisms to help students overcome them. For this purpose we carried out behavioral, brain imaging and intervention studies focusing on a previously demonstrated obstacle in mathematics education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 35 publications
2
46
0
Order By: Relevance
“…These observations confirm that the presence or absence of particular mathematical knowledge does not directly produce structure substitution. Our data supports the idea of the main role that control mechanisms play in the reasoning and interpretation process (Giroux and Ste-Marie 2001;Masson et al 2012;Stavy and Babai 2010).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These observations confirm that the presence or absence of particular mathematical knowledge does not directly produce structure substitution. Our data supports the idea of the main role that control mechanisms play in the reasoning and interpretation process (Giroux and Ste-Marie 2001;Masson et al 2012;Stavy and Babai 2010).…”
Section: Discussionsupporting
confidence: 91%
“…Stavy and Babai (2010) used the method of brain imaging to analyse the process of solving certain geometric problems. Their results showed that while the mathematical concepts at play were the same in all problems, there was a tendency for a different part of the brain to be more activated than the rest depending on the geometric condition.…”
Section: Literature Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…A key element of learning any new concepts is the need to overcome strongly held prior beliefs about a domain before new knowledge can be effectively assimilated 14,15 . Thus, a major challenge in mathematics and science education is the need for children to inhibit pre-existing beliefs or superficial perception in order to engage in acquiring and applying new and counterintuitive knowledge 13,16,17,18 . Because of the importance of this process in scientific reasoning, many researchers have focused on investigating the naïve concepts that children and adults hold about phenomena in various scientific domains.…”
Section: Conceptual Change In Science and Mathematicsmentioning
confidence: 99%
“…However, the same team of researchers (Houdé et al, 2000) also found that adults who were trained to overcome a perceptual bias leading to wrong answers in a deductive logic task showed more activation after rather than before training in frontal lobe areas involved in inhibition. Other researchers (Stavy & Babai, 2010) found that the activation of brain areas related to inhibition is also correlated to the capacity to correctly answer counter-intuitive questions about the perimeter of figures.…”
Section: Inhibitionmentioning
confidence: 96%